Anteseden Perilaku Pembelian Pakaian Mode Berkelanjutan di Jakarta - Amelia Yasmin Putri; Sri Vandayuli Riorini (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to examine global social identity, social media influence, green apparel knowledge, sustainable fashion perception and electronic word-of-mouth (E-WOM). From the research, a total sample of 140 was collected using a questionnaire with the criteria of respondents having visited shopping centers in Jakarta, Indonesia and having experience shopping for clothes. The data analysis method used in this study is the Structural Equation Model (SEM) with AMOS software tools. The results of the study are (1) Global Social Identity has a significant positive influence on Green Apparel Knowledge (2) Social Media Influences do not have a significant positive influence on Green Apparel Knowledge (3) Green Apparel Knowledge has a significant positive influence on Sustainable Fashion Apparel Perception ( 4) Sustainable Fashion Apparel Perception has a significant positive influence on the Electronic-Word Of Mouth.